Perlindungan Hukum Pedagang Kecil dari Keberadaan Franchise Minimarket (Studi Peraturan Walikota Bandar Lampung Nomor 17 Tahun 2009) - Rissa Afni Martinouva (KEADILAN PROGRESIF, 2017)
Small traders owned and managed by entrepreneurs who have capital to lower middle. In the development of small traders, present business activity trade with minimarket franchise formats such as "Alfamart and Indomart" many spread evenly on each side of the road. Two types of businesses that have a different format is an attempt to distribute the product needs of everyday people. The method used normative juridical and observations. Reasons given legal protection against small traders such as franchise minimarket has a more modern service system, proof of the transaction, the more spacious, equipped with air conditioning, parking lot, promotions, discounts and provide shopping convenience. Many entrepreneurs founding owners of high capital, founding more and more, it is feared will kill the business enterprises of small traders around the business place. Small traders do not have the advantage and can not compete as a franchise minimarket. Governments protect small traders with few rules. Legal protection in the form of exclusion of small traders through the rule of law Act No. 5 of 1999 because they would not do the trade monopoly. The legal protection of small traders and minimarket franchise is set in a presidential decree number 112 of the Republic of Indonesia in 2007. The exception and the setting is not enough to protect small traders. Forms of legal protection of small traders hereafter specifically governed by the regulation of the mayor number 17 in 2009 in the Bandar Lampung City. Regulations on the establishment permit, distance, hours minimarket operations in opening franchise is a form of legal protection provided by the government to small traders.